THE EFFECT OF QUALITY PERCEPTION, REFERENCE GROUPS AND SALES PROMOTION ON IMPULSE BUYING OF MOBILE LEGENDS ONLINE GAME PLAYERS - Aldrino, Aldrino; Mario, Mario; Yohanes, Jonathan; Samatha, Felisca; Falatehan, Falatehan (Jurnal Manajemen, 2025)
Online gaming has become a global phenomenon that affects many aspects of life, including cultural, social and economic. One of the most popular online games is Mobile Legends, which belongs to the Multiplayer Online Battle Arena (MOBA) genre. The game has attracted millions of players around the world, including Indonesia, which accounts for about 50% of the total global players. Mobile Legends offers 5 vs 5 team-based gameplay, where each player controls a character or hero with unique roles and skills. Its popularity is also supported by competitive elements through tournaments and player community groupings. This study aims to explore the influence of Mobile Legends on player behaviour, communication patterns, and its impact on learning achievement. The study found that in-game social interactions can create toxic behaviour patterns, especially if players are in a negative reference group. Conversely, a positive reference group can provide a constructive influence. In addition, the intensity of playing this game has a significant impact on students learning achievement. The results show that players who cannot manage their playing time tend to experience a decline in academic performance, while players who can divide their time effectively can benefit from mental relaxation and happiness while playing. Further studies also show that the experience and comfort of playing Mobile Legends influence the intensity of purchasing in-game items. Therefore, further research with a more in-depth approach is needed to explore other factors that play a role in players interaction with the Mobile Legends game.